OPPRESSION AGAINST THE BLACK IN JAMES GARTNER'S GLORY ROAD MOVIE: A MARXIST APPROACH - MARTARINA, NIKA (2010)
The object of this research is the movie entitled Glory Road by James Gartner. The major problem of this study is how oppression against the black is reflected in the movie James Gartner's Glory Road based on Marxist approach. It occurs because there are two social classes, namely upper class, whites, as oppressors and lower class, blacks, as oppressed. The writer employs qualitative research method. In this method, the writer uses two data resources namely primary and secondary data sources. The primary data source is the movie James Gartner's Glory Road itself. The secondary data sources is related to the primary data, such as author's biography, website related to class conflict and many other data related to class conflict and many other data related to this research. The method of data collection is note-taking and image-capturing and the technique of data collection is descriptive technique. The study comes to the following conclusion: Firstly, based on structural analysis, it is evident that in this movie, James Gartner conveys a message that appreciation and reward should be based on achievement rather than racial supremacy. Secondly, based on the Marxist analysis, it is clear that in this movie, James Gartner describes the struggle of the blacks for equality in all aspects including sport, which is begun by several conflicts to reach their goal.